Status Gizi dan Sosial Ekonomi sebagai Penyebab Anemia Ibu Hamil - Evi Martha; Herlena Hayati (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The prevalence of maternal anemia is 37.1%, with 51.5% among them of maternal anemia as an indirect cause of maternal death. This study aims to determine nutritional and socioeconomic status as the causes of maternal anemia in AM Parikesit Tenggarong Hospital in 2017. This study is quantitative and qualitative using a cross-sectional design and Rapid Assessment Procedures (RAP). Quantitative using descriptive-analytic methods with a sample of 214 pregnant women. Qualitative using content analysis with 37 informants. The results showed there was a relationship (p = 0.027) between nutritional status with maternal anemia after being controlled with homeownership, history of delivery assistance, pregnancy spacing, and parity. Socioeconomic factors such as homeownership having a role in iron intake. The results of qualitative research indicate the consumption of heme vegetable is the highest consumption among anemic mothers, besides the low compliance of pregnant women in consuming Fe tablets. On the contrary, pregnant women who did not anemic consumption of animal heme is their daily consumption, and almost entirely obedient in the consumption of Fe tablets. Cross program and sectoral cooperation are needed, providing cheap and affordable sources of carbohydrate and protein by the middle-lowe economic community, providing a source of vitamins and minerals that help the process absorption of Fe.